Agility and change of direction in soccer: differences according to the player ages - Fiorilli, G.; Mitrotasios, M.; Iuliano, E.; Pistone, E.M.; Aquino, G.; Calcagno, G.; Di Cagno, A. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The goal of this study was to compare the changes of direction speed (CODS) and reactive agility (RA) in soccer players of different ages, in order to optimize the best training of these skills.